The Old Kiavak Site, Kodiak Island, Alaska, and the Early Kachemak Phase - Clark, Donald W. (ARCTIC, 1996)
Excavations from 1963 on Kodiak Island, Alaska represent an early regional phase of the Kachemak tradition called "Early Kachemak" and a local phase called "Old Kiavak." Information remains insufficient to fully outline this phase of the third and fourth millennium B.P. owing to poor recovery of organic artifacts and a very sparse inventory. Comparisons with other Early Kachemak components found on Kodiak Island and elsewhere show considerable geographic variation. The Old Kiavak phase exemplifies one local phase. Radiocarbon dating indicates that occupation of the site extended back in time from approximately 2200 B.P. to 3500 B.P. No major temporal gap existed between Old Kiavak and the antecedent Ocean Bay tradition. Evidence for technological continuity from the Ocean Bay tradition to the Kachemak tradition has been found at site AFG-088 on Afognak Island of the Kodiak group. The Ocean Bay-Kachemak transition tentatively is called the Afognak phase. Radiocarbon dating indicates that this phase began slightly earlier than the Old Kiavak phase, but the two probably overlapped. The seven millennia of cultural continuity thus accorded to Kodiak Island have significant implications for the history of the northern North Pacific region and Eskimo genesis. Des fouilles effectuées en 1963 dans l'île Kodiak en Alaska représentent une phase régionale précoce de la tradition Kachemak appelée «Kachemak précoce» et une phase locale appelée «Kiavak ancienne». En raison d'une faible récupération d'artefacts organiques et d'un très petit inventaire, on ne possède pas suffisamment d'information pour définir pleinement cette phase du troisième et du quatrième millénaire BP. Des comparaisons avec d'autres composants de la Kachemak précoce trouvés dans l'île Kodiak et ailleurs révèlent une importante variation géographique. La phase de la Kiavak ancienne est typique d'une phase locale. La datation au radiocarbone indique que l'occupation du site a duré d'environ 2200 BP à 3500 BP. Entre la tradition de la Kiavak ancienne et ...